On the benthic hydroids from the Scotia Arc (Southern Ocean): new insights into their biodiversity, ecology and biogeography - Joan, J.; Álvaro, L. (Polar Biology, 2015)
The Scotia Arc, located between the Antarctic Peninsula and the southern tip of South America, is an important zone from the biogeographic point of view. Its benthic biodiversity has been extensively documented with a few exceptions, among others, the hydroid fauna, which constitutes one of the major components of the benthic Antarctic communities. With the aim of increasing the data in three different but complementary fields of knowledge (namely biodiversity, ecology and biogeography), an unpublished collection obtained during the German Antarctic expedition ANTARKTIS XIX/5 (LAMPOS) with the RV Polarstern in 2002 has been studied. A total of 45 species of benthic hydroids, belonging to 9 families and 20 genera, was found. Forty of them, including Halecium stoloniferum sp. nov. and Schizotricha discovery sp. nov., were identified to the species level. Leptothecata was by far the most dominant order with 42 species, while Anthoathecata was only represented by 3 species. Fifteen species (38 %) are endemic to the Antarctic region and 31 (78 %) restricted to Antarctic and/or sub-Antarctic waters. Schizotricha southgeorgiae, Halecium elegantulum and Sertularella argentinica are reported for the second time, whereas Schizotricha jaederholmi, Antarctoscyphus gruzovi and Sertularella jorgensis for the third time. New original autoecological data concerning the use of the substrate, reproductive phenology and bathymetric range of the inventoried species are provided. Published